IN MEMORIAM Anton Kivik (08.11.1928–26.05.2007) (Eesti Arst, 2008)
Eesti arstkonda on tabanud raske kaotus. Meie hulgast lahkus 26. mail 2007 erudeeritud kolleeg dotsent Anton Kivik.Eesti Arst 2008; 87(2):165